Performance anxiety among student table tennis players - Yumna Wahyuningsih; Ibnu Fatkhu Royana; Galih Dwi Pradipta (CV Rezki Media, 2025)
Background: Anxiety is a common psychological factor that significantly affects athletic performance, especially in competitive settings. Student-athletes face dual pressures from academic responsibilities and athletic commitments, making them vulnerable to performance anxiety that can impair focus, concentration, and decision-making. Objectives: This study aims to analyze performance anxiety among table tennis athletes in the Student Activity Unit (UKM) of Universitas PGRI Semarang and to examine differences in performance evaluation outcomes based on sources from internal and external factors. Methods: A comparative quantitative design with a cross-sectional approach was used. Fifty athletes participated (n=25 assessed by internal factors, n=25 assessed by external factors). Anxiety/performance was measured using a self-report questionnaire consisting of 15 Likert-scale items (1-5 scale) validated by three sport psychology experts. Data were analyzed using one-way ANOVA after confirming normality (Shapiro-Wilk test) and homogeneity (Levene's test). Results: The internal group had a higher mean score (M = 3.64, SD = 0.86) compared to the external group (M = 3.07, SD = 0.86). ANOVA revealed a statistically significant difference, F(1,48) = 4.92, p = 0.031, η² = 0.093, with an estimated Cohen's d of approximately 0.66, indicating a medium effect size. These findings indicate that anxiety factors affect athletes' performance, with internal factors tending to score higher than external factors. Conclusions: This study concludes that anxiety affects the performance of table tennis athletes in the Student Activity Unit (UKM) at Universitas PGRI Semarang. Specifically, internal factors such as self-confidence and perfectionism have been proven to have a greater impact than external factors.